Manajemen Kasus Bagi Anak Autis Di Unit Layanan Rehabilitasi Sosial Anak Penyandang Disabilitas (ULRS APD) Sentra Mulya Jaya Jakarta - Hani Oktaviyani; Sokhivah Sokhivah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Case management in social work is a method of providing services carried out by a professional social worker by assessing the needs of the client and the client's family appropriately. The problem of autistic children is quite serious, this can be seen from the increasing number of autistic children from year to year. In responding to existing problems, the role of social workers is needed to carry out assessments and interventions on the problems of autistic children by using a holistic approach to their social environment. Therefore, ULRS APD Sentra Mulya Jaya serves children with autism using a case management approach. This research aims to determine the stages of case management in handling autistic children at ULRS APD Sentra Mulya Jaya Jakarta and to find out the obstacles of social workers in handling autistic children at ULRS APD Sentra Mulya Jaya Jakarta. Data collection techniques in this research were observation, interviews and documentation using a qualitative approach. The results of this research show that there are several stages of case management in ULRS APD, namely engagement, assessment, planning, intervention, monitoring, evaluation, termination, and follow up (follow up). The obstacles experienced are limited human resources, especially the social worker profession and a lack of understanding of parents accompanying children with autism.